Justiça, gênero e famílias: pensando uma teoria da justiça com e contra Axel Honneth - Stanley Souza Marques (2021)
Western political thought has kept in anonymity - despite feminist criticisms - the domesticfamily space, its specificities, democratic transformations, internal injustices, and publicpolitical implications. And this is because it is assumed or postulated, almost everywhere, the idea, certainly more presupposed than problematized, that the public and the domestic are sufficiently separate and sufficiently distinct domains. However, Axel Honneth, in Freedom's Right, deviates from such a theoretical arrangement that still dominates the field of political theories and theories of justice. He not only reorients the theory of justice towards the normative tendencies inherent in the social world but also delves into intimate and familial relationships, converging with some of the historical claims of feminism. Thus, he promotes rather than prohibits reflection on the connections between justice and families, which are shown there as unavoidable. Honneth places issues such as love, intimacy, care, and sexuality at the center of the justice debate because all of them are subject to democratic selfdetermination. Therefore, this thesis operates within the framework of Honneth's theory of justice. It proposes a “normative reconstruction” of the sphere of families in Brazil, as if responding to a demand from Honneth´s project. Such a “critical-reconstructive” endeavor, however, leads to a specific framing of the growth and diversification of paid female labor and changes in educational practices, two of the phenomena recognized by Honneth. The movement here is twofold; it follows and diverges from the Honnethian diagnosis, considering the Brazilian scenario: the sphere of families indeed embodies and realizes, as Honneth asserts, an aspect or facet of the general value of freedom. An internal recognition principle is activated there, by which individuals orient themselves, mobilize their everyday political struggles, experience a form of social freedom that is now more or less available, and can critically evaluate intrafamily practices. However, it is also true that the mass entry of women into the labor market and changes in child-rearing practices have not been able to subvert some of the “ideological forms of recognition” of women, contrary to Honneth's diagnosis. While it dismantles the ideological model of the full-time housewife, highly esteemed in the last century, especially among middle-class and upper-class families, the same cannot be said for the emotional appeals to being a “good” mother, which should be understood for what they truly are, namely, “ideological forms of recognition”, both from the past and the present, no matter how modified they may seem at first glance.